2015
DOI: 10.9755/ejfa.v27i4.19912
|View full text |Cite
|
Sign up to set email alerts
|

Camel colostrum: Nutritional composition and improvement of the antimicrobial activity after enzymatic hydrolysis

Abstract: Camel colostrum collected within 24 h after parturition was analyzed for physicochemical and microbiological composition. The average contents of fats, dry matter, mineral matter and proteins were 1.71±0. 51, 199.55±16.93, 9.75±0.5 and 143.42±36.42 gL -1 , respectively. Microbiological analysis of colostrum samples showed richness in yeasts and Lactic acid bacteria and absence of coliforms. The good microbial quality of camel colostrum is due to a number of antimicrobial molecules such as immunoglobulins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…Camel milk displayed a higher antibacterial effect compared with that of CaWH-III and CoWH-III; however, the results did reach statistical significance. This result is similar to that of Jrad [29]. Many studies have shown that hydrolysates with high biological activity comprise low molecular weight peptides [30,31].…”
Section: Ultrafiltration Fractionation (Uf) Of Cawh and Cowhsupporting
confidence: 86%
“…Camel milk displayed a higher antibacterial effect compared with that of CaWH-III and CoWH-III; however, the results did reach statistical significance. This result is similar to that of Jrad [29]. Many studies have shown that hydrolysates with high biological activity comprise low molecular weight peptides [30,31].…”
Section: Ultrafiltration Fractionation (Uf) Of Cawh and Cowhsupporting
confidence: 86%
“…Camel is the desert ship in our country; it is one among the animals mentioned in Quran as a miracle of the God (16). The nutrients, immunoglobulins and growth factors that present in the camel colostrum are very essential for regeneration of defect tissues, especially the bioactive factors (3). For all these reasons, we design this project to evaluate histologically the effect of camel colostrum extract as a biological treatment for healing of auricular cartilage defects.…”
Section: Discussionmentioning
confidence: 99%
“…Colostrum is differ from mature milk by its nutritional contain and immunological composition. In the matter of fact, camel colostrum contains more protein, nonprotein nitrogen, vitamins, minerals, and ash than milk (3). IgG1, IgG2, and IgG3 are the main sub-classes' immunoglobulins which are presented in camel colostrum (4).…”
Section: Introductionmentioning
confidence: 99%
“…BP interfere in the metabolic regulation and modulation, and they are used as potential nutraceutics and as ingredients of functional foods. Also, they present important properties such as antioxidants, chelators, anticoagulant, antimicrobial, hypocholesterolemic, growth stimulating of probiotic bacteria and antihypertensive (Sun et al, 2014;Zeineb et al, 2015;Przybylski et al, 2016;Sabbione et al, 2016;Marques et al, 2015;Titov et al, 2016;Lafarga et al, 2016).…”
Section: Antioxidant Capacity Of Egg Milk and Soy Protein Hydrolysatmentioning
confidence: 99%